(untitled) (Research, Society and Development, 2021)
The State, as an intervener, must organize urban planning through the execution of public policies. In this context, good land governance is important for the balanced territorial development of the municipality, since the local municipality’s failure to observe the best territorial planning generates chaotic urban meshes. Cities are usually born hugging their rivers, and citizens in search of a better life agglomerate in villages, neighborhoods and communities. Therefore, there is a need to organize the common space of all, and the State legislates on general rules to regulate the urbanization of cities. However, for a better land use planning it is required: interest in acting, qualified employees and resources to implement efficient and effective public policies, especially in municipalities with up to 20,000 inhabitants where the master plan is not required. The study aims to analyze the academic productions that deal with municipal governance in order to identify whether good land governance is a priority for the manager of small towns. This is a literature review that seeks to analyze land governance in small towns. For a better delimitation, searches of scientific journals were carried out. As results with respect to good territorial governance it was found that the inertia of the manager and the lack of technical capacity of his team does not prioritize good territorial governance.